Biological monitoring of exposure to toluene diisocyanate - Sennbro, Carl-Johan; Lindh, Christian H.; Tinnerberg, Håkan; Welinder, Hans; Littorin, Margareta; Jönsson, Bo AG (Scandinavian Journal of Work, Environment & Health, 2004)
' ' OBJECTIVES ': 'Toluene diisocyanate (TDI) is used in the manufacture of polyurethane and is a potent inducer of diseases of the airways. In this study, 2,4- and 2,6-toluenediamine in hydrolyzed urine and plasma were evaluated as biomarkers of exposure to 2,4- and 2,6-TDI, respectively. ' ' METHODS ': 'For 81 exposed workers from nine different plants, the personal 8-hour time-weighted-average exposure to TDI was monitored by a filter method with 1-(2-methoxyphenyl)piperazine. In parallel, urinary samples (U1) were collected during the last 4 hours of the workshift. On a different occasion, blood samples and additional urinary samples (U2) were collected from the exposed workers, and also from a reference group consisting of 121 unexposed workers. The biomarker levels were determined in urine and plasma by the use of alkaline hydrolysis. ' ' RESULTS ': 'There were strong associations between the personal air and biomarker levels, with correlation coefficients in the range of 0.75-0.88 for the U1 samples and in the range of 0.50-0.78 for the plasma samples. By weighted linear regression, the relations were calculated between the air and biomarker levels. The slopes of the obtained regression curves ranged from 1.8 to 2.7 m3/l for air-urine and from 2.2 to 2.9 m3/l for air-plasma, and the intercepts were all close to the origin of the coordinates. Through the extrapolation of these regression curves, biological exposure limits were calculated. ' ' CONCLUSIONS ': 'The biological monitoring methods and strategies presented in this report are useful for assessing exposure to TDI in practice.
Keywords: biological exposure index; biological monitoring; biomarker; exposure; occupational exposure limit; polyurethane; protein adduct; toluene diisocyanate